Association of proton pump inhibitor use with renal outcomes in patients with coronary artery disease - Nam-Jun Cho; Chi-Young Choi; Samel Park; Sang-Ho Park; Eun Young Lee; Hyo-Wook Gil (Kidney Research and Clinical Practice, 2018)
Background : Several studies have suggested that proton pump inhibitor (PPI) use is associated with adverse renal outcomes, but obvious evidence for this association is lacking. We investigated the association between PPI use and adverse renal outcomes in patients who had undergone percutaneous coronary intervention. Methods : Of the 1,284 patients hospitalized for percutaneous coronary intervention between January 2007 and May 2012, 934 patients with baseline estimated glomerular filtration rate greater than 60 mL/min/1.73 m² were enrolled. Multivariable Cox models were used to examine whether PPI use was associated with acute and chronic adverse renal outcomes. Results : In adjusted time-dependent Cox models, PPI use was associated with acute kidney injury (hazard ratio [HR], 1.46; 95% confidence interval [95% CI], 1.05-2.02), especially in patients aged 65 years or younger (HR, 2.08; 95% CI, 1.09-3.96) or in patients with diabetes (HR, 2.00; 95% CI, 1.23-3.25). In multivariable Cox models, the association between duration of PPI use and chronic kidney disease development was not statistically significant (HR of heavy users, 1.50; 95% CI, 0.61-3.67), but a longer duration of PPI use was associated with mild renal progression in patients younger than 65 years (HR of heavy users, 2.24; 95% CI, 1.09-4.60). Conclusion : Our results suggest that PPI use increases the risk of AKI development, and that PPI use is more significantly associated with acute and chronic renal injuries in younger patients.